Distinguishing Plasma Lupus Anticoagulants from Anti-Factor Antibodies Using Hexagonal (II) Phase Phospholipids - Rauch, Joyce; Tannenbaum, Marion; Janoff, Andrew S (Thrombosis and Haemostasis, 1989)
The association of lupus anticoagulant antibodies with thrombosis, thrombocytopenia, and multiple spontaneous abortions underlines the importance of diagnostic assays which are able to distinguish these antibodies from anti-factor antibodies and factor deficiencies, as all three prolong in vitro coagulation assays measuring activated partial thromboplastin time (APTT). Heparin also prolongs the APTT assay and often interferes with the detection of lupus anticoagulant activity. The present study describes a direct and simple dilute APTT assay in which plasma is preincubated with hexagonal (II) phase phosphatidyl ethanolamine (PE). Using this system, the lupus anticoagulant antibody activity of 10 randomly selected plasmas from SLE patients was inhibited by 81.2-99.5%, while prolongation of the APTT assay by 6 different anti-factor antibody-containing plasmas, 5 factor deficient plasmas, and 6 heparin-containing plasmas remained unaffected. Inhibition was dependent on epitopes exposed when PE was presented in the hexagonal (II) phase. This data suggests that hexagonal (II) PE is specifically recognized by lupus anticoagulant antibodies in SLE patients and may play a role in the etiology of the disease.
Keywords: Anti-factor antibodies; Hexagonal (II) phase lipids; Lupus anticoagulants; Activated partial thromboplastin time; Phospholipids; Anti-phospholipid antibodies